Beautiful redemption / 4. - Garcia, Kami (Garcia, Kami. Beautiful creatures novel, 2012)
Ethan Wate finally begins to like his small Southern town of Gatlin after meeting Lena Duchannes, but when he is forced to leave everything behind, both Ethan and Lena risk everything to be together again.